MOTIVASI PETANI DALAM BUDIDAYA RUMPUT LAUT DI DESA SERIWE KABUPATEN LOMBOK TIMUR - Widiyanti, Ni Made Nike Zeamita; Setiawan, Rifani Nur Sindy (Fakultas Pertanian Universitas Mataram, 2024)
Seaweed is an important and strategic commodity for the community. Seaweed cultivation activities can generate income for farmers. Therefore, it needs to get special attention from related parties. Farmer motivation is one factor that needs to be considered because it can affect seaweed cultivation activities carried out by farmers. Indirectly, it can also affect the production activities and income of farmers. The objectives of this study, namely (1) Knowing the level of motivation of farmers in seaweed cultivation in Seriwe Village, East Lombok Regency and (2) Analyzing the factors that influence the level of motivation of seaweed farmers in Seriwe Village, East Lombok Regency. The analysis method used is the Rank Spearman analysis method. Respondents were seaweed farmers in Seriwe Village, East Lombok Regency. Based on the results of the analysis obtained the level of motivation of farmers in conducting seaweed cultivation is high, which is 76%. Variables that correlate to the level of farmer motivation are income, capital availability, number of family dependents, market availability and price. While variables that do not correlate with motivation, namely: age, education, farming experience, and availability of facilities and infrastructure.